Трансгресія у п’єсі “Трамвай Бажання” Т. Вільямза та у фільмі “Все про мою матір” П. Альмодовара: стратегії інтермедіальності - Дроздовський, Д. (Слово і Час, 2012)
У статті проаналізовано стратегії інтермедіальності на прикладі п’єси “Трамвай Бажання" Теннессі Вільямза та фільму “Все про мою матір” Педро Альмодовара. Визначено принципи інтертекстуальної взаємодії двох текстів у компаративістичній площині. Окреслено форми залучення п’єси Т. Вільямза в кінотекст за допомогою трансгресії як ідейно-тематичного та сюжетно-композиційного комплексу (трансформації, транссексуальності, трансплантації). In the paper, the author analyzes the strategies of 'ntermediality in the play “A Streetcar Named Desire” by Tennessee Williams and in the movie "Todo sobre mi madre” by Pedro Almodovar. The principles of intertextual interaction of the two texts have been discussed in comparative mode. The forms of integration of T. Williams’s play into the movie text have been outlined and explained by transgression as a thematological and plot-compositional complex (with such subcategories as transformation, transsexuality and transplantation).